2019
DOI: 10.3390/atoms7030090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Oxygen Transport Coefficient in the Aditya Tokamak Using the Radial Profile of O4+ Emissivity and the Importance of Atomic Data Used Therein

Abstract: Oxygen impurity transport in the typical discharges of the Aditya tokamak was investigated using emissivity radial profile of emissivity of the spectral line (2p3p 3D3–2p3d 3F4) at 650.024 nm from the Be-like oxygen ion. This O4+ spectral line was recorded using a 1.0 m multi-track spectrometer capable of simultaneous measurements from eight lines of sight passing through the plasma. The oxygen transport coefficients were determined by reproducing the experimentally measured emissivity profiles of O4+, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Large value of the oxygen impurity diffusion coefficient at the plasma edge, ∼45 m 2 s −1 , has been obtained as compared neo-classical transport and is explained using fluctuation-induced transport [25], which is mainly ion temperature gradient driven transport. Not only that it is found that obtained diffusion coefficient depends on the atomic data and the atomic processes included in the code [24]. The results from newly developed code have been also compared with the study done using STRAHL for benchmarking of the newly developed code.…”
Section: Investigation Of Oxygen Impurity Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Large value of the oxygen impurity diffusion coefficient at the plasma edge, ∼45 m 2 s −1 , has been obtained as compared neo-classical transport and is explained using fluctuation-induced transport [25], which is mainly ion temperature gradient driven transport. Not only that it is found that obtained diffusion coefficient depends on the atomic data and the atomic processes included in the code [24]. The results from newly developed code have been also compared with the study done using STRAHL for benchmarking of the newly developed code.…”
Section: Investigation Of Oxygen Impurity Transportmentioning
confidence: 99%
“…Various studies on the impurities behaviour and plasma properties, such as impurity influx, reduction of plasma Z eff after Li coating of wall, etc, have been regularly carried out using diagnostics based on PMT (photomultiplier tube), PMT array, and the multiple PMT modules in the visible range. The plasma ion temperature, rotation and spatial profile of brightness measurement have been done routinely using a high-resolution spectrometer having 1 m focal length and equipped with a CCD (charge coupled device) camera [22] to understand the physical mechanism behind intrinsic rotation [23] and to study the impurity transport [24][25][26], respectively. A fast visible imaging camera coupled with a fiber bundle has been also used to measure the plasma shape and size and also to study the plasma disruption.…”
Section: Introductionmentioning
confidence: 99%
“…The collisional-radiative (CR) model is used to study in various types of plasmas [19][20][21][22][23]. The CR model works well in the intermediate density regime i.e., ∼ 10 10 -10 15 cm −3 .…”
mentioning
confidence: 99%
“…The CR model of the ADAS code and database has been used for the study of the laser plasma, the tokamak plasma, etc. [19][20][21][22][23]. The ADAS is an interconnected set of computer codes and data collections for modelling the radiating properties of ions and atoms in plasmas.…”
mentioning
confidence: 99%